Exploring the key drivers of crop yields in Morocco – a systematic review - Achli, Soumia; Ongoma, Victor; Epule, Terence Epule; Dhiba, Driss; Salih, Wiam; Ousayd, Lahcen; Chehbouni, Abdelghani (Frontiers in Agronomy, 2025)
IntroductionMorocco's agricultural sector faces significant socio-environmental challenges that threaten food security and economic development. A comprehensive assessment of these challenges is crucial for informed decision-making at both national and farm scales. This study aims to identify and analyze key drivers influencing crop yields in Morocco, with a focus on grain crops, by integrating climatic, socio-economic, and biophysical factors.MethodsA systematic review of 135 peer-reviewed and grey literature sources published between 1990 and 2024 was conducted. The review examines both climatic and non-climatic factors affecting crop yields, particularly for wheat, a staple in Morocco’s food system.ResultsPrecipitation emerged as the primary driver of crop yields, with approximately 15.6% of the literature analyzed emphasizing its impact. Other significant factors include irrigation, fertilization, water stress, temperature, technical efficiency, soil properties, conservation agriculture, insects and pests, sowing date, drought, crop varieties and genetics, diseases, herbicides, and extreme climatic events. These drivers interact in complex ways, with precipitation and irrigation playing pivotal roles in mitigating water stress and enhancing crop productivity.DiscussionThe findings highlight the intricate dependencies between climatic and agronomic factors affecting Morocco's grain production. Understanding these interactions is essential for policymakers and farmers to develop strategies that enhance agricultural sustainability and resilience. This study provides a foundation for impact-based analysis and evidence-based decision-making to improve productivity and ensure food security in Morocco.